The Official Perspective in Academe University Administrators' Views on Authority - Lunsford, Terry F.; California Univ., Berkeley. Center for Research and Development in Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This study analyzes sources of instability in the formal authority of administrators in large U.S. universities, the perspectives by which campus executives attempt to cope with these problems, and the effects on present and future executives' legitimacy. The findings of a survey of attitudes held by 526 executives in 69 large and prestigious universities indicated that "institutionally conservative" responses were found to be associated with business-finance job specialties, lack of an earned doctorate, lack of graduate study in arts and sciences, minimal experience in teaching and research, length of time as an academic administrator, lack of current teaching duties, participation in interuniversity administrative meetings, Republican political preference, religiosity, conventional Christian religious preference, and age. Attitudes, backgrounds, and current involvements were reported for four major executive jobs: presidents, business-finance executives, academic vice-presidents or deans, and student affairs executives. In addition, the dynamics of recent breakdowns in campus executives' legitimacy were analyzed, and suggestions made about the probable future of university administration. (Author/AF)
Contract Number: OEG-6-10-106.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Problems; Deans; Leadership Responsibility; Presidents; Administrator Attitudes; Administrator Characteristics; College Administration; Higher Education